WEBSITE USABILITY, SATISFACTION, LOYALTY, SECURITY PERCEPTION, TRUST AND WORD OF MOUTH IN E-COMMERCE BUSINESS - Chintia Rosdiana Dewi; Gede Sri Darma (Universitas Pendidikan Nasional, 2014)
The explosive growth of the e-commerce nowdays, especially in Indonesia, iscontinuously increasing the competitiveness between the e-commerce agents involved in it. Theappearance of the internet reduced the search costs and provided the high flowof informationobtained by the consumer, made it more difficult to increase the consumerloyaltyin an onlinebusiness. Word-of-mouthis regarded as a powerful tool for advancementof the competitiveadvantage in e-commerceaimed by marketing managers. Due to this issue, this researchanalyzes the role of website usability, satisfaction, loyalty, security perception and trust indeveloping positive word-of-mouth in e-commerce business. It was foundthat website usabilityhad a significant positive effect on customer satisfaction and security perception, whileconsumer satisfactionoffered a significant positive effect on loyalty and positive word-of-mouth.It also was found that security perception builtpositive effect to trust significantly. The trust itself, had the role on increasing the consumer loyalty value, unfortunately it was notthesignificant one. And as expected, loyalty was significantly related to positive word-of-mouth.In addition, customer satisfaction, website usability and loyalty was found to be the top threefactors whichcontributed biggest number of the total effect on the role to increasing the positiveword-of-mouth in e-commerce. For further, several conclusions, managerial implications andpossibilities for future research are arise.Keywords : website usability, satisfaction, loyalty, security perception, trust, word of mouth,e-commerce